Is photography-based taxonomy really inadequate, unnecessary, and potentially harmful for biological sciences? A reply to Ceríaco et al. (2016) - Thorpe, Stephen E. (Zootaxa, 2017)
An opinion piece was recently published in this journal which, remarkably, is less than one page in length, but has 493 authors (signatories) and has gained over 15 thousand reads on ResearchGate in a very short time. Ceríaco et al. (2016) argue for a blanket ban to be imposed on the uncommon practice of basing new species descriptions in zoology on photographic evidence only of the animal. I herein aim to show that their argument is a non sequitur, i.e. their stated reasons do not support their desired conclusion.